Identification of Salacia chinensis (Celastreaceae) using Leaf Anatomical Characters. (International Journal of Food and Nutritional Sciences, 2023)
The objective of the present study was to observe the anatomical features ofSalacia chinensis, to study the unique characters in the family, to observe the shape, structureand arrangement of cells which will help us to find out the adulterated drugs. Salacia chinensisof Celastraceae family was a promising medicinal plant with great economic potential.